A Computational Study to Elucidate the Phytochemicals as An Antagonist Against Pruritis in Psoriasis - Prateeksha Vijayakumar; Samiksha Bhor (International Journal of Bioinformatics and Computational Biology, 2023)
Objective: Psoriasis is a chronic, non-contagious, auto-immune skin disorder that causes inflammation, pain, and itching in the affected areas. The etiology of this condition is not entirely understood, and while there are treatments available to manage the symptoms, there is currently no cure. The Transient receptor potential cation channel, subfamily Vanillin, member 3 (TRPV3), present in keratinocytes, allegedly had a part in the development of psoriasis-related pain and itching. Specifically, this report's main goal was to identify a potential antagonist (an anti-pruritic medication) that could desensitize TRPV3, by blocking its activity and reducing these symptoms. Methods: An in-silico approach was carried out by docking the chosen twelve phytocompounds based on the recent pre-clinical studies, with the TRPV3 target using Auto dock 4.2 after optimizing the crystal structure of the protein and preparation of ligands. Bio via discovery studio was used to visualize the 3D and 2D interactions and draw a conclusion from the results obtained. Results: Almost all compounds showed good binding energy values, but Hypericin, Kaempferol, Quercetin, and Emodin showed stronger binding affinities and proved to be efficient antagonists against TRPV3. Conclusion: Further clinical studies and improvements are needed in the near future to confirm these natural compounds as useful antipruritic agents in the treatment of psoriasis.
Keywords: ADME analysis; Autodocking; Keratinocytes; Pharmacokinetic profiling; Phytochemicals; Psoriasis vulgaris; TRPV3; Virtual screening; anti-psoriatic drug; molecular docking; phytocompounds; pruritis